Fibronectin is deposited by injury-activated epicardial cells and is necessary for zebrafish heart regeneration - Wang, Jinhu (2013)
Unlike adult mammals, adult zebrafish vigorously regenerate lost heart muscle in response to injury. The epicardium, a mesothelial cell layer enveloping the myocardium, is activated to proliferate after cardiac injury and can contribute vascular support cells or provide mitogens to regenerating muscle. Here, we applied proteomics to identify secreted proteins that are associated with heart regeneration. We found that Fibronectin, a main component of the extracellular matrix, is induced and deposited after cardiac damage. In situ hybridization and transgenic reporter analyses indicated that expression of two fibronectin paralogues, fn1 and fn1b, are induced by injury in epicardial cells, while the itgb3 receptor is induced in cardiomyocytes near the injury site. fn1, the more dynamic of these paralogs, is induced chamber-wide within one day of injury before localizing epicardial Fn1 synthesis to the injury site. fn1 loss-of-function mutations disrupted zebrafish heart regeneration, as did induced expression of a dominant-negative Fibronectin cassette, defects that were not attributable to direct inhibition of cardiomyocyte proliferation. These findings reveal a new role for the epicardium in establishing an extracellular environment that supports heart regeneration.